120 MeV Ag ion irradiation induced intermixing, grain fragmentation in HfO2/GaOx thin films and consequent effects on the electrical properties of HfO2/GaOx/Si-based MOS capacitors. Issue 1 (2nd January 2020) - Vinod Kumar, K.; Arun, N.; Mangababu, A.; Ojha, Sunil; Nageswara Rao, S. V. S.; Pathak, A. P.
Abstract : On p-type Silicon (100) substrates GaO x (150 nm) and HfO2 (30 nm) thin films have been synthesized using the RF magnetron sputtering method. After 120 MeV Ag SHI irradiation, ion-induced inter-diffusion/inter-mixing of Hf and Ga elements has been observed which leads to the development of inter-mixing of layers at the interfaces. As deposited films have randomly oriented large, inhomogeneous and non-uniform grains with an average size of 34.5 nm, while at the highest fluence, the formation of homogeneous and uniform individual spherical grains with an average size of 13.8 nm has been observed. Furthermore, HfO2 /GaO x /Si-based MOS capacitors have been fabricated and the consequent effects on the electrical properties of these devices have been discussed in detail.